Chagas Disease - Heukelbach, Jorg; Ramos Jr., Alberto Novaes; de Sousa, Andrea Silvestre (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Despite being described for the first time more than 110 years ago, Chagas disease (caused by the parasite Trypanosoma cruzi) persists as one of the most neglected tropical diseases. This persistent neglect of those affected by this disease is evidenced by the ongoing scientific evidence gaps, the difficulty of incorporating new diagnostic and treatment technologies into the market, and public health failures to ensure timely access to diagnosis and treatment associated with the development of consistent surveillance and control actions. As a result, there is a high burden of morbidity and mortality, and poor quality of life, poverty, stigma, and a fear of death persist for affected people, both in endemic areas in Latin America, and in non-endemic areas. This book spans a variety of disciplines and contributes significantly to reducing the gap in scientific knowledge on Chagas disease, towards achieving the Sustainable Development Goals by 2030.